THE EFFECT OF ROOTING MEDIA ON THE GROWTH OF MALAY APPLE (Syzygium malaccense L.) SEEDLINGS FROM STEM CUTTINGS - Lestari Handayani Lestari; Ananti Yekti; Rajiman Rajiman (Politeknik Pertanian Negeri Samarinda, 2022)
This study aims to determine the effect of the type of planting medium in the propagation of Malay apple cuttings. The research design used is random design non-factorial grouping that consist of 5 levels of treatment for cuttings rooting media types, i.e. soil (1), soil + compost (1:1), soil + compost + chaff charcoal (1:1:1), sand + compost + chaff charcoal (1:1:1), and compost (1) with 5 repetitions and each replication consists of 25 experimental units, and each experimental unit consists of 15 samples and 3 spare plants, so there are 450 plants. The research was conducted from February to July 2022. The parameters observed include the time of shoot emergence, sprout percentage, root length, seed height, root volume, and the percentage of life. Data analysis used ANOVA (analysis of variance) and if there was an effect, then continued with the tukey’s HSD (Honestly Significant Difference) test with a level of 5%. The results showed that rooting media mixed with soil + compost + chaff charcoal or mixed media of sand + compost + chaff charcoal could increase the percentage of survival, seedling height, root length, and root volume of malay apple seedlings from stem cuttings.